“Do You Feel Safe at the Border?” An Intermedial Pedagogy for Sensing Communities of Shared Fate - Glanville, Erin (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2019)
This article considers the limitations of 1990s humanitarian and diaspora frames to mediate a sense of the border that moves beyond securitization and yet remains accountable to refugee claimant advocacy. As an alternative, this article explores an intermedial pedagogy for bringing critical border studies into the realm of embodiment and feeling. Drawing on teaching and research interviews, I consider how asking “do you feel safe at the border?” produces an effective challenge to persistent public emotions conflating national “borders” with the need for “security.” In complex ways, this kind of storytelling can bring into view, what Melissa Williams calls, “communities of shared fate” that exist across the spectrum of legal statuses, tapping in to extant feelings rooted in real, shared vulnerability at the border.